Association between TyG-BMI and BPH in a national prospective cohort study - Bing Li; Zhiqiang Zhang; Chao Sun; Yaodong Sun; Junping Li; Xiaoqiang Liu (Scientific Reports)
Abstract This study aims to explore the relationship between the Triglyceride Glucose Body Mass Index (TyG-BMI) and the risk of developing benign prostatic hyperplasia (BPH). Utilizing data from the China Health and Retirement Longitudinal Study (CHARLS), we included 3301 men aged 45 and above. We analyzed the association between TyG-BMI and the risk of developing BPH using multivariable logistic regression and restricted cubic spline models. During the 4-year follow-up period, 268 cases of BPH were identified. There was a positive correlation between TyG-BMI and the risk of BPH (OR 1.22, 95% CI 1.08–1.38, p < 0.001), with a significant dose-response relationship (P < 0.001). Stratified analyses indicated that the impact of TyG-BMI on BPH risk was consistent across various subgroups. There is a linear positive correlation between TyG-BMI and the risk of developing BPH. Managing TyG-BMI levels may help reduce the risk of BPH.